2022
DOI: 10.3390/ijerph192114173
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Consequences of Short-Form Video (SFV) Addiction amongst Adolescents in China: Stress-Coping Theory Perspective

Abstract: As a hedonic technology, short-form videos (SFVs) have attracted numerous users. However, one related problem that merits research is SFV addiction, especially among adolescents due to their immature self-control abilities. Although recent research has discussed the formation process of SFV addiction from psychological needs and the SFV features perspective, scarce attention has been paid to investigating the relationship between stress and SFV addiction, as well as the relationship between SFV addiction and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, the vast array of information available through various mobile applications can cause individuals to become lost in an overwhelming sea of knowledge and develop an addiction to information acquisition. Additionally, short videos [17,35] and mobile games [36,37] have emerged as coping mechanisms for some individuals in response to stress. However, the findings of the present study indicate that in the case of high-stress populations, it is imperative to prioritize the examination of social media addiction and information addiction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the vast array of information available through various mobile applications can cause individuals to become lost in an overwhelming sea of knowledge and develop an addiction to information acquisition. Additionally, short videos [17,35] and mobile games [36,37] have emerged as coping mechanisms for some individuals in response to stress. However, the findings of the present study indicate that in the case of high-stress populations, it is imperative to prioritize the examination of social media addiction and information addiction.…”
Section: Discussionmentioning
confidence: 99%
“…According to CSM, predictions are that the 10-29 age group will be more likely to spend both, more time and money, on short videos and it will result in overconsumption. Many studies have confirmed the deleterious effects of such overuse Mu et al, 2022;Qin et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…In the past COVID-19 pandemic, social isolation and closure have made Short video addiction(SVA) a hot topic of discussion [ 1 ]. As a social software that allows users to create and share their own beautiful moments, short videos, with their fragmented model and rich personalized content, have rapidly become a worldwide hit form of entertainment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%